2011
DOI: 10.1016/j.transproceed.2011.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Extracellular-Type–Kyoto Solution and Perfadex as a Preservation Solution in a Pig Ex Vivo Lung Perfusion Model: Impact of Potassium Level

Abstract: The pig EVLP system was not affected when ET-K was used instead of PX as the flush/preservation solution. The initial 200 mL of effluent should be discarded when using the ET-K to ensure that the potassium level does not increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Other groups have successfully conducted perfusion experiments with slaughterhouse organs including kidneys, 14,49 livers, 50,51 hearts, 15,52 and lungs. 12,13,53 …”
Section: Discussionmentioning
confidence: 99%
“…Other groups have successfully conducted perfusion experiments with slaughterhouse organs including kidneys, 14,49 livers, 50,51 hearts, 15,52 and lungs. 12,13,53 …”
Section: Discussionmentioning
confidence: 99%
“…Avsar et al (13) concluded in a pig model that lung architecture and oxygenation were satisfactory using hyperoncotic nonalbumin solution. Comparisons of Perfadex with other perfusates, such as the Kyoto perfusates (14), showed no difference in pulmonary vascular resistance (PVR) and oxygenation. Initially, Steen et al (9) as well as others (15,16) popularized cellular perfusion for EVLP.…”
Section: Perfusate and Preservative Compositionmentioning
confidence: 99%
“…The routine change of perfusate remains debatable. There are data suggesting that the removal of a quantity of the perfusate may avoid hyperkalemia (14).…”
Section: Perfusate and Preservative Compositionmentioning
confidence: 99%